MELACAK AKAR PAHAM TEOLOGI ISLAM DI INDONESIA - M Ridwan Lubis (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
Ahlussunnah wal Jamaat was an icon of theological understanding used in the past as Islamic approach for Muslims in Indonesia referring to preservation of balance condition. On the other hand, this theological understanding was effective enough to reach islamization process without causing social upheaval; however it was weak to transform social system. Then community had conversion into Islam but their social system in economy, politics, education, and law were controlled by local tradition or western modernism manipulation. This situation changed after 1970s when reorganization in teaching Islam occurred by introducing the distinction between Islam teaching and Islamic culture. However, these ideas were getting reaction from intellectual Muslims. The greatest goal of Ahlussunnah wal Jamaah theology was formulating a synergy among the Islamic discourse, democracy, and nationality at NU Congress in Situbondo in 1984, so Indonesia as a country based on Pancasila was considered as the final form of Islam toward the statehood concept.